Complete Left Bundle Branch Block in Acute Coronary Syndrome with ST Segment Elevation: Epidemiological Features - ZOUZOU, Hanane (Clinical Medicine And Health Research Journal, 2023)
Background: Complete left bundle branch in acute coronary syndrome with ST segment elevation is not common, but known as a sign of poor prognosis. Several international studies had reported its incidence and related mortality, but its epidemiological data is lacking in Algeria. Aims: The main objective of our study is the determination of the frequency of complete left bundle branch block in acute coronary syndrome with ST segment elevation, the secondary objective was the analysis of its predictive factors and related mortality. Methods and materials: In this prospective study, conducted in the cardiology department of Hussein Dey hospital (Algiers-Algeria), 467 patients with acute coronary syndrome with elevated ST segment (87 women and 380 men) were enrolled between 28 February 2014 and 16 July 2015. The average age is 60 ± 13 years; at admission, a Holter recorder was attached for continuous ECG monitoring during 48 hours. Kruskal’s ANNOVA or H tests were used for comparison of quantitative variables, χ2 test or Fisher’s exact test, were used for qualitative variables, all tests were performed with 1st species risk of 5%. Results: The frequency of complete left bundle brunch block is 1.7 % (8 patients), CI 95%: [0.5%-2.9%], multivariate analysis identified the two independent predictors: diabetes type 1, and Angiotensin Receptor-Blockers as current treatment. Despite the risk of mortality expressed by Hazard Ration (HR) is 4.7, but remains not significant: CI95%: [0.62-36], p = 0.134; however, the risk of ventricular fibrillation occurrence is high, with relative risk (RR) at 7.17, CI 95 %: [2.70-19.03], p = 0.007. Conclusion: Complete left bundle brunch block is not common in acute coronary syndrome with elevated ST segment, its predictive factors according to our study are: Diabetes type 1 and Angiotensin Receptor-Blockers as current treatment. The high-risk mortality in the left bundle brunch block group isn’t significant; however the risk of ventricular fibrillation occurrence is high.